In-vitro differentiation of human embryonic stem cells into spinal cord neural stem cells. Issue 12 (5th July 2022) - Chen, Xueying; Zhao, Tianyi; Ke, Naiyu; Qian, Yutong; Wang, Wanrong; Liu, Lihua; Liu, Chao
Abstract : In-vitro differentiation of human embryonic stem cells into spinal cord neural stem cells (NSCs) can help researchers better understand the cellular processes associated with spinal cord development and regeneration, and provide therapeutic strategies for spinal cord disorders. However, effective and consistent methods for the generation of human spinal cord NSCs are rare. Objective of the study is to establish methods for the in-vitro induction and long-term maintenance of human spinal cord NSCs. H9 cells were treated with neural induction medium for 10 days under single-cell seeding condition, followed by treatment with neural maintenance medium and replacement with NSC medium after five passages. The identity of the generated cells was determined by immunofluorescence, immunoblotting, and cleavage under targets and tagmentation (CUT&Tag) assays. After the neural induction, OCT4, an embryonic stem cell marker, was significantly reduced, whereas NESTIN and PAX6, two NSC markers, were clearly increased. After the neural maintenance, most of the H9-derived cells consistently expressed NESTIN and PAX6 together with SOX1 and HOXC9, two spinal cord markers. The Homer known motif enrichment results of the CUT&Tag assay confirmed the expression of HOXC9 in the H9-derived spinal cord NSCs, which can be maintained for more than 40 days under an in vitro culture system. This study sheds new light on effective induction and maintenance of human spinal cord NSCs.